Political microtargeting: Towards a pragmatic approach - Peter Aagaard; Selma Marthedal (Internet Policy Review, 2023)
It has become increasingly popular for scholars to investigate the technology of political, personal microtargeting (PMT). We review a sample of 62 research articles in the field of political PMT and argue that these studies can be grouped according to different orientations: an interpretative orientation, either expressing hopes for voter mobilisation or strong concerns for democracy and voter manipulation, or a descriptive orientation, viewing PMT as a supplement to the traditional elements of political campaigns. We argue that these two orientations must continuously be mixed thoughtfully in a pragmatic approach that addresses public concerns on highly empirical grounds to avoid technological myths.
Keywords: 300; Political campaigns; Microtargeting; Social media; Data campaigning; Personal data protection